Positive Solutions for Boundary Value Problems with Fractional Order - Benchohra, Mouffak; Hedia, Benaouda (International Journal of Advanced Mathematical Sciences, 2013)
In this paper we investigate the existence of at least one, two positive solutions by using the Krasnoselskii fixed-point theorem in cones for nonlinear boundary value problem with fractional order.